Histological Diagnosis of Implant-Associated Pathologies - Krenn, Veit.; Perino, Giorgio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
Histological evaluation of the periprosthetic soft and osseous tissues is an important analytical tool. Its standardization is essential to generate accurate and reproducible data which allow comparisons for academic institutions, arthroplasty registries, and government regulatory agencies worldwide. It is also part of multidisciplinary evaluation of orthopedic implant failures and provides valuable information to be integrated with the clinical data, allergological tests, radiological exams, microbiological analysis, and biomechanical assessment of the implant wear.
Introduction -- Interdisciplinary Diagnosis of Joint Prosthesis Pathology -- Clinical Approach on Synovial like Interface Membranes -- Standardized Collection and Processing of Tissue Samples -- Future Perspectives -- Conclusion.
Keywords: Medicine; Radiology; Orthopedics; Pathology; Medicine & Public Health; Surgical Orthopedics; Pathology; Imaging / Radiology